In vitro preliminary screening of bioactive compounds of different parts of Adansonia digitata L. a globally endangered tree - Samatha Talari; Rama Swamy Nanna (International Journal of Phytomedicine, 2015)
The present investigation was undertaken to screen the different parts of Adansonia digitata L. for the presence of bioactive compounds. The preliminary phytochemical screening was performed by using various solvent extracts of different parts such as leaf, seed, fruit wall and floral parts of A. digitata. The phytochemical analysis of the dry seeds, leaf, floral extracts, fruit wall and bark of stem was carried out to determine the presence of bioactive compounds using the standard qualitative procedures. The phytochemical analysis revealed that all the solvent extracts of different parts were rich in possession of flavonoids, alkaloids, glycosides, tannins, sterols, phenols, saponins, coumarins and quinones. From the present study it can be concluded that extracts of different parts of this valuable tree can be utilized in the preparation of various active principles of medicines to alleviate many diseases.